2016
DOI: 10.1044/2015_jslhr-l-15-0022
|View full text |Cite
|
Sign up to set email alerts
|

Story Goodness in Adolescents With Autism Spectrum Disorder (ASD) and in Optimal Outcomes From ASD

Abstract: Purpose: This study examined narrative quality of adolescents with autism spectrum disorder (ASD) using a well-studied "story goodness" coding system. Method: Narrative samples were analyzed for distinct aspects of story goodness and rated by naïve readers on dimensions of story goodness, accuracy, cohesiveness, and oddness. Adolescents with high-functioning ASD were compared with adolescents with typical development (TD; n = 15 per group). A second study compared narratives from adolescents across three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
1
10
0
2
Order By: Relevance
“…Other authors used a narrative retelling, based on a video-tape, to elicit spontaneous speech (Diehl et al 2009). However, as already mentioned in the introduction, building a coherent narrative is also known to present difficulties for people with ASD (Baixauli et al 2016;Stirling et al 2014;Banney et al 2015;Canfield et al 2016)-in fact, this is the reason why it features in the ADOS-2 (Lord et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors used a narrative retelling, based on a video-tape, to elicit spontaneous speech (Diehl et al 2009). However, as already mentioned in the introduction, building a coherent narrative is also known to present difficulties for people with ASD (Baixauli et al 2016;Stirling et al 2014;Banney et al 2015;Canfield et al 2016)-in fact, this is the reason why it features in the ADOS-2 (Lord et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Arnold et al, 2009;) that a more ecologically valid assessment of pragmatic language ability may be found via assessment of language in naturalistic contexts, with the full range of cognitive and social demands this places on the participants. Canfield et al (2016) reported that coding schemes used in their study failed to detect systematic differences in narrative quality between children with and without autism, but naïve raters could still detect subtle difficulties in the narratives of children with autism nonetheless. It is therefore necessary for linguistic analysis to focus on detailed aspects of conversation, in order to identify the subtle ways in which individuals with autism have difficulty in conversing (Arnold et al, 2009): modifying the approach of conversation analysis may offer us a means to do this.…”
Section: Methodological Approach and Predictionsmentioning
confidence: 95%
“…Previous research has also based assessment of pragmatic ability (i.e. narrative ability) on segments from the ADOS (Canfield et al, 2016). While the ADOS includes codes for pragmatic language ability (e.g.…”
Section: Methodological Approach and Predictionsmentioning
confidence: 99%
“…Across each of these studies, participants in the LAD group scored in the average range or higher, with performance similar to (or higher than) that of the TD group. Experimental behavioral studies have revealed similar performance in LAD and TD groups for ratings of likeability and broader autism phenotype 17 , and for a variety of pragmatic language abilities 18 21 . This behavioral work provides a foundation for further exploration of the range of possible outcomes (including questions about how to define an optimal outcome 22 ), and the nature of the neural systems that support such sharp changes in developmental trajectories 23 .…”
Section: Introductionmentioning
confidence: 97%